Analysis of Smoking Behavior Risk Factors in Adolescent through Health Belief Model Approaches - Anhar, Vina Yulia; Arifin, Syamsul; Rahman, Fauzie; Ridwan, Agus Muhammad; Bohari, Bohari (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Teenagers who smoke are very susceptible to product degradation which is seen in the low quality of human resources. Identification of risk factors needed as a first step before health interventions to prevent and reduce smoking rates in adolescents. AIM: This study aims to analyze the risk factors for smoking behavior in adolescents through the health believe model approach. METHODS: The design of this study is observational using a cross-sectional approach with the sample size, namely, 156 respondents. The instrument planned to be used in this study is a questionnaire that has been tested for validity and reliability. This study has received permission from relevant parties, including having received approval from the ULM FK Ethics Commission. The variables to be studied are, dependent: Smoking and independent behavior: Gender, knowledge, attitude, parental influence, peer influence, and cigarette advertising. The data analysis used Chi-square test and Fisher’s exact test with a significance level of p < 0.05. RESULTS: Frequency distribution, 139 (89.1%) respondents do not smoke, 81 (51.9%) respondents were female, 147 (5.8%) respondents are well-informed, and 141 (90.4%) respondents have a positive attitude, the number of respondents who are not affected by the smoking behavior of the elderly is 142 people (91%). Number of respondents who are not affected by peer smoking behaviors is 150 people (96.2%) and 144 people (92.3%) of the respondents were exposed to cigarette advertisements in the high category. Statistical tests show that the variables that have a significant relationship with smoking behavior are gender (p = 0.000), attitude (p = 0.000), parental influence (p = 0.000), and cigarette advertising (p = 0.000). CONCLUSIONS: There are four variables which have a relationship with smoking behavior, namely, there is a relationship between gender, attitude, the influence of parents, and cigarette advertising with smoking behavior.